Preparation of SOP for Container Checking at PT Kepri Depo Logistik - Krisnawati Sitanggang (MID Publisher International, 2023)
This study report discusses the procedures for preparing container checks and making standard operating procedures, especially in checking customer order criteria at PT Kepri Depo Logistik. The background of this writing is the frequent return of containers by customers due to non-compliance with ordering criteria, checks that are still carried out sober and supported by repair processes that have not run well while the company does not have clear procedures related to the ordering and checking system. The purpose of this study is to find solutions to problems that occur in companies related to checking and ordering activities that have not been effective and efficient. This study used Descriptive Method. The results suggest that companies should make Standard Operating Procedures (SOPs) regarding ordering and checking activities in which a list of container criteria checks can be made into a written format before being sent to customers.